Art of happiness at work / by Lama Dalai - Dalai Lama (London, 2003)
Over the past several years, Howard Cutler has continued his conversations with the Dalai Lama, asking him the questions we all want answered about how to find happiness in the place we spend most of our time-at work. Once again, Dr Cutler brings forward seminal studies and asks the Dalai Lama to respond, probing his wisdom by posing theses significant questing: How does the relationship between our personal values and those of our employers affect happiness?
Keywords: Happiness